On prohibitions and permissions in criminal law (2018)
In this article a philosophical analysis of the doctrine is made on the relationship between the categories “typical penalties” and “unlawfulness” elaborated by the Germanist criminal dogmatic, having as framework the doctrine of the deontological operato